Keeping an Eye on Decellularized Corneas: A Review of Methods, Characterization and Applications - Andrew Hopkinson; James B. Rose; Siobhán E. Dunphy; Laura E. Sidney; Samantha L. Wilson (Journal of Functional Biomaterials, 2013)
The worldwide limited availability of suitable corneal donor tissue has led to the development of alternatives, including keratoprostheses (Kpros) and tissue engineered (TE) constructs. Despite advances in bioscaffold design, there is yet to be a corneal equivalent that effectively mimics both the native tissue ultrastructure and biomechanical properties. Human decellularized corneas (DCs) could offer a safe, sustainable source of corneal tissue, increasing the donor pool and potentially reducing the risk of immune rejection after corneal graft surgery. Appropriate, human-specific, decellularization techniques and high-resolution, non-destructive analysis systems are required to ensure reproducible outputs can be achieved. If robust treatment and characterization processes can be developed, DCs could offer a supplement to the donor corneal pool, alongside superior cell culture systems for pharmacology, toxicology and drug discovery studies.